Quinacrine and curcumin synergistically increased the breast cancer stem cells death by inhibiting ABCG2 and modulating DNA damage repair pathway. (February 2020) - Nayak, Deepika; Tripathi, Neha; Kathuria, Deepika; Siddharth, Sumit; Nayak, Anmada; Bharatam, Prasad V.; Kundu, Chanakya
Graphical abstract: Highlights: Quinacrine and Curcumin synergistically caused apoptosis in breast cancer stem cell like cells (CSCs). Quinacrine and Curcumin inhibit the ABCG2 transporter activity. Curcumin increases the uptake of Quinacrine in CSCs enriched side population (SP) cells. Quinacrine binds more efficiently in DNA than Curcumin for causing DNA damage in cells. Quinacrine and Curcumin inhibit the induction of base excision repair pathway in the SP cells. Abstract: Cancer stem cell like cells (CSCs) present a challenge in the management of cancers due to their involvement in the development of resistance against various chemotherapeutic agents. Over expression of ABCG2 transporter gene is one of the factors responsible for drug resistance in CSCs, which causes efflux of therapeutic drugs from these cells. The development of inhibitors against CSCs has not achieved any significant success, till date. In this work, we have evaluated the anti-proliferative activity of curcumin (Cur) and quinacrine (QC) against CSCs using in vitro model system. Cur and QC synergistically inhibited the proliferation, migration and invasion of CSCs enriched side population (SP) cells of cigarette smoke condensate induced breast epithelial transformed (MCF-10A-Tr) generated metastatic cells. Cur + QC combination increased the DNA damage and inhibited the DNA repair pathways in SP cells. Uptake of QC increased in Cur pre-treated SP cells and this combination inhibited the ABCG2 activity by the reduction of ATP hydrolysis in cells. In vitro DNA binding reconstitution system suggests that QC specifically binds to DNA and caused DNA damage inside the cell. Decreased level of ABCG2, representative cell survival and DNA repair proteins were noted after Cur + QC treatment in SP cells. The molecular docking studies were performed to examine the binding behaviour of these drugs with ABCG2, which showed that QC (-53.99 kcal/mol) and Cur (-45.90 kcal/mol) occupy a highly overlapping interaction domain. This suggested that in Cur pre-treated cells, the Cur occupied the ligand-binding site in ABCG2, thus making the ligand binding site unavailable for the QC. This causes an increase in the intracellular concentration of QC. The results indicate that Cur + QC combination causes CSCs death by increasing the concentration of QC in the cells and thus causing the DNA damage and inhibiting the DNA repair pathways through modulating the ABCG2 activity.